Is boldness towards predators related to growth rate in naïve captive-reared Arctic char ( Salvelinus alpinus )? - Laakkonen, Mika VM; Hirvonen, Heikki (Canadian Journal of Fisheries and Aquatic Sciences, 2007)
Previous studies have shown that the antipredator responsiveness of fish degenerates through generations in captive breeding. However, detailed knowledge of the underlying mechanism is still largely lacking. We tested the hypothesis that hatchery fish supposedly selected for faster growth in the hatchery environment are bolder towards predators than their slower-growing conspecifics. This was examined by comparing the antipredator behavior of predator- naïve fast- and slow-growing individuals of a captive-bred Arctic char (Salvelinus alpinus) population to chemical cues from natural predators burbot (Lota lota) and pikeperch (Sander lucioperca). As behavioral responses depended on char body size, we compared boldness towards predators of size-matched fast- and slow-growing char. We found no differences in four behavioral antipredator traits between size-matched groups of fast- and slow-growing char. According to these results, boldness to predator cues is not related to individual growth rate in captive-bred Arctic char.